Bribery as a Hidden Driver of Corporate Financial Misreporting: An Integrative Systematic Review and a Multi-Level Propositional Framework - Palete, Siprianus; Pagalung, Gagaring; Said, Darwis (International Review of Management and Marketing, 2026)
Bribery and corporate financial misreporting are two of the most consequential forms of organizational deviance affecting capital-market integrity, yet their respective literatures have developed in substantial isolation. This systematic literature review synthesizes 52 peer-reviewed articles published between 2001 and 2025, predominantly drawn from Scopus Q1 journals across accounting, management, economics, political science, business ethics, and criminology, to examine how bribery operates as a hidden driver of corporate financial reporting behaviour. Reporting follows the PRISMA 2020 standard. The review is organized around five questions concerning (1) how the bribery–misreporting relationship has been conceptualized, (2) the mechanisms linking the two, (3) contextual moderators, (4) methodological approaches and their limitations, and (5) knowledge gaps. The synthesis identifies three causal architectures: a direct-concealment pathway in which disguising illicit payments necessitates accounting manipulation; an indirect governance-erosion pathway in which corrupt environments weaken controls and normalize deviance; and a reverse and co-evolutionary pathway in which misreporting generates off-book resources that finance future bribery. Building on this evidence, the review advances a multi-level framework and seven testable propositions, the centrepiece of which is an institutional-substitution argument: concealment through misreporting is most necessary precisely where formal institutions are strong enough to demand it, and least necessary where corruption can be transacted openly. The review contributes an integrative theory of the bribery–misreporting nexus, a critical methodological appraisal, and actionable guidance for regulators, auditors, and boards on integrating anti-bribery and anti-fraud controls.